Struktur Mise En Scene Budaya Batak Toba Pada Film Pariban Dari Tanah Jawa 2019 Sutradara Andibachtiar - Nurul Khasanah; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to determine Toba Batak culture in the Pariban idol film from Java using mise en scene. In the film Pariban, idols from Java depict many of the meanings in each story such as the characters, language and culture of the people through a qualitative descriptive approach. It is hoped that this research will be able to convey the meaning implied in the film Pariban Idol from Java. The type of method in this research uses qualitative research methods. Qualitative is field or interpretive research. The object of his research is the Pariban film from Java. The type of data source used by the author in this research is primary data obtained from the film itself and then observing mise en scene elements from several scene pieces or scenes needed for research purposes. The data collection technique in this research is in the form of documentation by searching for data regarding matters related to films via the internet and books that are related to this research.